2019
DOI: 10.1177/0969733019833126
|View full text |Cite
|
Sign up to set email alerts
|

Phronesis of nurses: A response to moral distress

Abstract: Background: As moral action could help nurses reduce moral distress, it is necessary to carry out qualitative research to present the experiences in which nurses apply moral action. Aim: To describe and analyze the phronesis applied by nurses in the face of moral distress. Research design: The research participants were invited to participate in in-depth interviews. The research materials were based on the stories described by the research participants and recorded by means of first-person narrative. Narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…There is a general expectation that nurses are morally courageous, especially in challenging health care situations, such as during the COVID-19 pandemic. How and to what extent nurses show moral courage when faced with moral distress is, however, hardly been investigated (19). We found two studies supporting the presence of moral courage in the majority of nurses (20,21).…”
Section: Introductionmentioning
confidence: 67%
“…There is a general expectation that nurses are morally courageous, especially in challenging health care situations, such as during the COVID-19 pandemic. How and to what extent nurses show moral courage when faced with moral distress is, however, hardly been investigated (19). We found two studies supporting the presence of moral courage in the majority of nurses (20,21).…”
Section: Introductionmentioning
confidence: 67%
“…10,13,17,19 It becomes visible as actions in accordance with one’s own values, such as telling the truth 19,24 and intervening in the shortcomings of the care environment. 14,17,23,44 The nurse’s personal qualities, such as empathy, 21 honesty, 19 perseverance, 13,15 and sensitivity to perceive the patient’s vulnerability 11 have been found to promote moral courage.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies of nurses’ moral courage have approached the concept using qualitative research designs. 1122 Studies have revealed that moral courage appears as a desire to protect patients and to defend their rights. 10,13,17,19 Studies have identified moral courage as a personal virtue.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 , 45 , 46 In nursing, research on moral courage has been fairly scarce, but it has increased in the last 10 years. The majority of studies have used qualitative research designs, 32 , 47 58 thus offering generalizable theoretical or inferential knowledge of moral courage, but not lending itself to measure the level and determinants of moral courage.…”
Section: Introductionmentioning
confidence: 99%